Akkermansia muciniphila suppressing nonalcoholic steatohepatitis associated tumorigenesis through CXCR6+ natural killer T cells - Li, Tao; Lin, Xinlong; Shen, Binhai; Zhang, Wujian; Liu, Yangyang; Liu, Hongbin; Wang, Ye; Zheng, Lijun; Zhi, Fachao (Frontiers in Immunology, 2022)
Gut microbiota play a crucial role in the development and progression of nonalcoholic steatohepatitis (NASH) and associated hepatocellular carcinoma (HCC). Akkermansia muciniphila was reported to inhibit inflammation-associated cancer in the intestine. The anti-NASH ability of A. muciniphila has recently been found. Thus, we were to investigate whether supplementation of A. muciniphila could prevent NASH-associated HCC. In a model we called STAM, male C57BL/6J mice were administered a single subcutaneous injection of 200 µg streptozotocin at 2 days after birth followed by high-fat diet to induce NASH and HCC (20 weeks of age). Faeces from mice and patients with NASH-related HCC were collected for 16S rRNA sequencing. STAM mice were orally administered either saline or A. muciniphila twice a day starting at 4 or 10 weeks of age. The effects of A. muciniphila on the immune responses were also evaluated. The abundance of faecal A. muciniphila was significantly decreased in patients and mice with NASH-related HCC. Administration of breast milk-isolated A. muciniphila (AM06) but not feces-isolated A. muciniphila (AM02) could improve NASH severity. Interestingly, breast milk-isolated A. muciniphila treatment suppressed the progression of NASH to HCC, accompanied with an increased hepatic CXCR6+ natural killer T (NKT) cell and decreased macrophage infiltration. The antitumor ability of A. muciniphila was not evident in NKT cell-deficient mice (CD1d-/- and CXCR6-/-). In vitro, A. muciniphila promoted the killing of hepG2 cells by NKT cells. Our study will provide theoretical basis for the application of A. muciniphila in the treatment of NASH and prevention for its progression to HCC.